Strategi Pengembangan Objek Wisata Pantai Bale-Bale Kampung Tua Bakau Serip, Kec. Nongsa, Kota Batam - Wahyudi Ilham; Dailami Dailami; Tirta Mulyadi; Tito Pratama (Tourism Scientific Journal, 2022)
This study aims to determine the strategy of object development Bale-Bale Beach tourism which is located in Nongsa District, Batam City. The research was conducted by identifying internal and external factors which were then assessed and analyzed, and development strategies were formulated by minimizing weaknesses and threats. Data analysis using SWOT analysis. The strength factors of Bale-Bale Beach attractions are: Bale-Bale Beach attractions have beautiful views, have beautiful natural panoramas, there are tourist attractions such as tourist attractions such as dances, mangroves, archery, etc. For weakness factors, namely: difficult to find tourist objects BALE BALE beaches because there are no clear instructions, lack of reliable managers and human resources who can speak foreign languages, Promotion of tourist attractions that are not good, Lack of cooperative relations between Tourism Villages and local governments. As for the opportunity factor: Cooperating with well-known Tour and Travel services located in Batam City, Absorbing labor in the area around tourism objects that can reduce unemployment and the active role of managers and the community. For threat factors, namely: There is competition between tourist objects in the Nongsa area, Environmental or beach pollution, There are no special products that can be used as souvenirs. The development strategies are: Maximizing promotion through online media and websites for Bale-Bale Beach tourism objects, Making prototypes or directions to tourist attractions, Expanding cooperation with sales bureaus, Establishing cooperation with local governments to jointly manage and develop tourism objects. In this case, using local workers in managing tourist objects, maintaining and developing attractions and facilities owned by tourist objects, maintaining and preserving the environment.